Land Equivalent Ratio of Cowpea–Sorghum Relay Intercrop as Affected by Different Cattle Manure Application Rates Under Smallholder Farming System - Cosmas Parwada (Frontiers Media S.A., 2021)
Poor soil fertility is a major challenge to crop production in the communal farming areas of Zimbabwe. Intercropping legumes and cereals is a common soil fertility management technology among the farmers. A 3-year field experiment was conducted to evaluate cowpea–sorghum relay intercropping advantages in response to different cattle manure application rates. A 3 × 4 factorial experiment laid in a completely randomized block design (CRBD) with three replicates was conducted. The treatments were three cropping systems (sorghum sole, cowpea sole, and cowpea–sorghum intercrop) and four cattle manure application rates (0, 50, 75, and 100%). Crop growth rate (CGR), grain yield, harvest index (HI), relative competitive ability of each crop, and land equivalent ratio (LER) were measured. Analysis of variance and non-linear regression analyses were done to determine the yield benefits of cowpea–sorghum intercrop and estimate the relative competitive ability, respectively. Application of >75% cattle manure in a cowpea–sorghum intercrop enhanced the sorghum grain yield (75%) and HI (125%) of unmanured cowpea–sorghum plots. Cowpeas had higher CGR (159.6, 166.7 and 149.5 g m−2 day−1 at 7, 21, and 35 days after planting, respectively) at >75% cattle manure application rates on both intercrop and sole cropping than sorghum but with lower grain yield (1.4 t ha−1). Intraspecific competitive stress in sorghum was reduced at a high (>75%) quantity of manure applied. The effects of the intraspecific competition in cowpea were stronger (0.693) on grain yield than biomass at >75% manure application rates. The LER was >1 in all the treatments and was highest (2.73) under the cowpea–sorghum relay intercrop without cattle manure. Cattle manure application at 75% in a cowpea–sorghum intercrop enhanced the grain yield in sorghum and vegetative growth in cowpeas. It is therefore recommended to use the >75% cattle manure application rate in the intercrop if one wants higher grain in sorghum and high biomass in cowpeas possibly for fodder. Further studies are recommended to quantify the rate of increase in available N under the cowpea–sorghum relay intercrop with >75% cattle manure application rates.